STUDYING THE â€œLEGAL FLOWSâ€ AS A MULTIDISCIPLINARY METHOD TO PROMOTE CONSTITUTIONALISM AS A COMMON PROPERTY OF MANKIND - Carducci, Michele; Bruno, Anna Silvia (European Scientific Journal, ESJ, 2014)
This paper tackles the problems concerned the constitutional comparison, paying special attention to the â€œlegal flowsâ€ in the Era of globalization of information and legal practices. With â€œlegal flowsâ€ we mean the communicative interactions that occur between the legal operators from different parts of the world. These â€œflowsâ€ produce â€œimitationsâ€, judicial dialogue, migrations of constitutional ideas, constitutional borrowing between various legal orders. The analysis of these dynamic phenomena requires two methodological needs: the transdisciplinarity opening to social history, to sociolinguistics and anthropology of communication; and the knowledge of the ideological dimensions of geopolitics and geography in the globalized Era. The comparison of â€œlegal flowsâ€ becomes a necessary tool for the contemporary education of each legal scholar, dealing him to be used to dialogue, to accept the â€œotherâ€, to understand the difficulties of the comparison and the respect of the complexity of cultures. This is the only way to promote constitutionalism as common property of mankind.